2014
DOI: 10.1021/am501119k
|View full text |Cite
|
Sign up to set email alerts
|

Cell Response to Nanocrystallized Metallic Substrates Obtained through Severe Plastic Deformation

Abstract: Cell-substrate interface is known to control the cell response and subsequent cell functions. Among the various biophysical signals, grain structure, which indicates the repeating arrangement of atoms in the material, has also proved to play a role of significant importance in mediating the cell activities. Moreover, refining the grain size through severe plastic deformation is known to provide the processed material with novel mechanical properties. The potential application of such advanced materials as biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 219 publications
2
70
0
Order By: Relevance
“…It was also demonstrated that nanostructuring of CP Ti enhances the attachment and spreading of human bone marrow-derived mesenchymal stem cells on the surface of CP Ti [11]. The literature on the effect of grain refinement on cell-substrate interaction has been thoroughly analyzed in a very recent review [12].There is a strong effect of nanostructuring on corrosion behavior of metallic materials.The fundamentals of grain size effect on corrosion properties were discussed in recent reviews [13,14]. Corrosion and subsequent metal ion release from dental implants in human body is affected by fretting [15] and the pH and composition of the media (e.g.…”
mentioning
confidence: 99%
“…It was also demonstrated that nanostructuring of CP Ti enhances the attachment and spreading of human bone marrow-derived mesenchymal stem cells on the surface of CP Ti [11]. The literature on the effect of grain refinement on cell-substrate interaction has been thoroughly analyzed in a very recent review [12].There is a strong effect of nanostructuring on corrosion behavior of metallic materials.The fundamentals of grain size effect on corrosion properties were discussed in recent reviews [13,14]. Corrosion and subsequent metal ion release from dental implants in human body is affected by fretting [15] and the pH and composition of the media (e.g.…”
mentioning
confidence: 99%
“…Ideally, an SPD involves subjecting the material to a high hydrostatic (three dimensional) stress state that creates plastic deformation of material [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]2018 sample in form of pure or simple shear without significantly changing its overall dimensions. The SPD basic principle is illustrated in Figure 1, where a solid body is hydrostatically loaded.…”
Section: Severe Plastic Deformation (Spd) Methods For Effective Biomementioning
confidence: 99%
“…ARB performs two functions simultaneously on the material; shear strain deformation and bonding of the stacked sheets. The number of ARB passes run is proportional to the magnitude of induced strain, smaller grain size, higher tensile strength and [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]2018 hardness of the material. Various works in the literature have reported the use of ARB to enhance biomedical titanium alloys with ultrafine grain and improved mechanical properties [6][12] [60].…”
Section: Accumulative Roll Bonding (Arb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Few comprehensive review articles focused on this topic have been published very recently [251,256,257]. In 2004, Webster and Ejiofor [258] provided the first evidence of increased osteoblast adhesion on Ti, Ti-6Al-4V alloy and Co-Cr-Mo compacts with nanometer compared to conventionally sized particles.…”
Section: Biocompatibilitymentioning
confidence: 99%